The model of Heyman and the statical and kinematical problems for masonry structures. (2019) - Angelillo, Maurizio
The study of masonry mechanics requires a methodological approach radically different from the ones used for ductile structures. The main criteria adopted for the design of the latter, such as strength, stiffness and elastic stability, have a minor role in masonry structures. Even if this peculiar behaviour is rather evident, this point of view is far from manifesting itself among structural architects and engineers. Indeed, the theory of Heyman, giving a modern turn to the old approach to masonry design by means of clear cut simplifications, is in sharp contrast with the sophisticated constitutive theories made possible by finite element methods and the use of super-computers. In these notes, the implementation of Heyman's model for masonry on a computer is introduced. In particular, we describe a simple method based on energy minimization allowing the evaluation of the combined effect of loads and settlements on real masonry structures.